2005
DOI: 10.1093/chemse/bji039
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Receptor Neurons in Two Heliothine Moth Species Responding Selectively to Aliphatic Green Leaf Volatiles, Aromatic Compounds, Monoterpenes and Sesquiterpenes of Plant Origin

Abstract: Moths of the subfamily Heliothinae are suitable models for comparative studies of plant odour information encoded by the olfactory system. Here we identify and functionally classify types of olfactory receptor neurons by means of electrophysiological recordings from single receptor neurons linked to gas chromatography and to mass spectrometry. The molecular receptive ranges of 14 types in the two polyphagous species Heliothis virescens and Helicoverpa armigera are presented. The receptor neurons are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 59 publications
4
55
0
Order By: Relevance
“…However, other environmental factors such as the effect of seasonality, the CO 2 level, the ozone level, mechanical stress and drought also have been studied (Blanch et al, 2007;Curci et al, 2009;McKinney et al, 2011;Penuelas and Staudt, 2010;Staudt et al, 2000Staudt et al, , 2002 and incorporated into emission models recently (Arneth et al, 2007;Arneth and Niinemets, 2010;Grote et al, 2010;Keenan et al, 2009). In the past decade, great efforts have been made to improve regional and global models which estimate the source strength of BVOCs and in particular of isoprenoids (Grote and Niinemets, 2008;Guenther et al, 2006;Niinemets et al, 2002;Schurgers et al, 2009;Zimmer et al, 2000). While there is a generally accepted empirical emission algorithm for isoprene, which has been established to be influenced by both temperature and light (Guenther et al, 1993(Guenther et al, , 2006, for monoterpenes the situation is more complex -with some monoterpene emitters responding to temperature, and others to both light and temperature (Fuentes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other environmental factors such as the effect of seasonality, the CO 2 level, the ozone level, mechanical stress and drought also have been studied (Blanch et al, 2007;Curci et al, 2009;McKinney et al, 2011;Penuelas and Staudt, 2010;Staudt et al, 2000Staudt et al, , 2002 and incorporated into emission models recently (Arneth et al, 2007;Arneth and Niinemets, 2010;Grote et al, 2010;Keenan et al, 2009). In the past decade, great efforts have been made to improve regional and global models which estimate the source strength of BVOCs and in particular of isoprenoids (Grote and Niinemets, 2008;Guenther et al, 2006;Niinemets et al, 2002;Schurgers et al, 2009;Zimmer et al, 2000). While there is a generally accepted empirical emission algorithm for isoprene, which has been established to be influenced by both temperature and light (Guenther et al, 1993(Guenther et al, , 2006, for monoterpenes the situation is more complex -with some monoterpene emitters responding to temperature, and others to both light and temperature (Fuentes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Guenther et al, 1995Guenther et al, , 2006Grote and Niinemets, 2008) as both enantiomers react at the same rates with ozone and OH. However, for the biosphere (insect and plants) the two enantiomers can be very different and distinct molecules that may elicit opposite responses in pollinators and predators alike (Rostelien et al, 2005;Tooker and Hanks, 2004). Furthermore, variation in the individual enantiomers in ambient air may have the potential to provide clues about variable monoterpene sources within the plant cover through their individual responses to stimuli, and thereby represents a means to better link current empirical models to internal plant processes.…”
Section: Introductionmentioning
confidence: 99%
“…The ORNs receptive to pheromones ) and many other semiochemicals (Shields & Hildebrand 2001) appear to be highly specialized for a narrow range of chemicals. Numerous neuro-ethological studies have indicated that the ORN response profile of a given species is directly related to its behavioral significance, thus conveying reliable information about relevant plant odors (Kaissling et al 1989;D'Ettorre et al 2004;Røstelien et al 2005). The responses of ORNs to these chemical signals can be monitored with electrophysiological recording techniques such as electroantennogram (EAG) and single sensillum recording (SSR) (Lee et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent comparative studies revealed OSNs with mainly conserved receptive ranges or conserved representation patterns of odorants in the first olfactory neuropil across species, with only little impact of speciesspecific life histories. In these studies, however, only species belonging to the same family [Nymphalidae (Carlsson et al, 2011;Ômura and Honda, 2009)], subfamily [Heliothinae (Rostelien et al, 2005;Stranden et al, 2003); Murinae (Johnson et al, 2009;Soucy et al, 2009)], or genus [Drosophila (de Bruyne et al, 2010;Stensmyr et al, 2003)] were investigated. Remarkable similarities in olfactory coding were also found across the ant Camponotus fellah, the bee Apis mellifera and the rat Rattus norvegicus, i.e.…”
Section: Introductionmentioning
confidence: 99%